A remark on the slice map problem. (1994) - Chō, Muneo; Huruya, Tadasi
Abstract : It is shown that there exist aσ -weakly closed operator algebraA ˜, generated by finite rank operators and aσ -weakly closed operator algebraB ˜ generated by compact operators such that the Fubini productA ˜ ⊗ ¯ F B ˜ contains properlyA ˜ ⊗ ¯ B ˜ .